Compounds from Terminalia mantaly L. (Combretaceae) Stem Bark Exhibit Potent Inhibition against Some Pathogenic Yeasts and Enzymes of Metabolic Significance - Marthe Aimée Tchuente Tchuenmogne; Thierry Ngouana Kammalac; Sebastian Gohlke; Rufin Marie Toghueo Kouipou; Abdulselam Aslan; Muslum Kuzu; Veysel Comakli; Ramazan Demirdag; Silvère Augustin Ngouela; Etienne Tsamo; Norbert Sewald; Bruno Ndjakou Lenta; et al. (Medicines, 2017)
Background: Pathogenic yeasts resistance to current drugs emphasizes the need for new, safe, and cost-effective drugs. Also, new inhibitors are needed to control the effects of enzymes that are implicated in metabolic dysfunctions such as cancer, obesity, and epilepsy. Methods: The anti-yeast extract from Terminalia mantaly (Combretaceae) was fractionated and the structures of the isolated compounds established by means of spectroscopic analysis and comparison with literature data. Activity was assessed against Candida albicans, C. parapsilosis and C. krusei using the microdilution method, and against four enzymes of metabolic significance: glucose-6-phosphate dehydrogenase, human erythrocyte carbonic anhydrase I and II, and glutathione S-transferase. Results: Seven compounds, 3,3′-di-O-methylellagic acid 4′-O-α-rhamnopyranoside; 3-O-methylellagic acid; arjungenin or 2,3,19,23-tetrahydroxyolean-12-en-28-oïc acid; arjunglucoside or 2,3,19,23-tetrahydroxyolean-12-en-28-oïc acid glucopyranoside; 2α,3α,24-trihydroxyolean-11,13(18)-dien-28-oïc acid; stigmasterol; and stigmasterol 3-O-β-d-glucopyranoside were isolated from the extract. Among those, 3,3′-di-O-methylellagic acid 4′-O-α-rhamnopyranoside, 3-O-methylellagic acid, and arjunglucoside showed anti-yeast activity comparable to that of reference fluconazole with minimal inhibitory concentrations (MIC) below 32 µg/mL. Besides, Arjunglucoside potently inhibited the tested enzymes with 50% inhibitory concentrations (IC50) below 4 µM and inhibitory constant (Ki) <3 µM. Conclusions: The results achieved indicate that further SAR studies will likely identify potent hit derivatives that should subsequently enter the drug development pipeline.